2015
DOI: 10.1021/je500975a
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric and Viscometric Studies of Amino Acids in Vitamin B6 Aqueous Solutions at Various Temperatures

Abstract: The densities and viscosities of glycine, l-alanine, l-valine, l-threonine, and l-arginine in (0.1 to 0.4) mol·kg–1 vitamin B6 aqueous solutions were measured and studied over the entire molality range at (293.15, 303.15, 313.15, and 323.15) K and atmospheric pressure. The apparent molar volume (V ϕ), limiting partial molar volume (V ϕ 0), and limiting partial molar volume of transfer (Δtr V ϕ 0) were obtained according to the experimental density data. The viscosity data were employed to determine the viscosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…Kumar et al 16 reported that in the aqueous solution of ampicillin drug, the hydration behavior of dipeptides of alanine gets modulated due to the dominance of ion−hydrophilic as well as hydrophilic−hydrophilic interactions. Haghani et al 17 on the behavior of amino acids in aqueous solutions of vitamin B6, Ma et al 18 found that ion−ion, ion−hydrophilic, and hydrophilic−hydrophilic interactions predominate. Thus, it may be quite interesting to study the intermolecular interactions among CFX and amino acids (glycine (GLY) and L-isoleucine (ILU)) in aqueous solutions as a function of temperature and concentration using volumetric, acoustic, calorimetric, and spectral studies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kumar et al 16 reported that in the aqueous solution of ampicillin drug, the hydration behavior of dipeptides of alanine gets modulated due to the dominance of ion−hydrophilic as well as hydrophilic−hydrophilic interactions. Haghani et al 17 on the behavior of amino acids in aqueous solutions of vitamin B6, Ma et al 18 found that ion−ion, ion−hydrophilic, and hydrophilic−hydrophilic interactions predominate. Thus, it may be quite interesting to study the intermolecular interactions among CFX and amino acids (glycine (GLY) and L-isoleucine (ILU)) in aqueous solutions as a function of temperature and concentration using volumetric, acoustic, calorimetric, and spectral studies.…”
Section: Introductionmentioning
confidence: 99%
“…Haghani et al from the investigations on amino acids in the aqueous solutions of sodium benzoate found that the hydrophobic–hydrophobic and ion–nonpolar group interactions dominate. From the volumetric and viscometric studies on the behavior of amino acids in aqueous solutions of vitamin B6, Ma et al found that ion–ion, ion–hydrophilic, and hydrophilic–hydrophilic interactions predominate.…”
Section: Introductionmentioning
confidence: 99%
“…Vitamins are the requisite organic compounds (micronutrients) that are not produced in ample amounts inside biological systems and have to be attained via diet or external supplements. Vitamin B3 (niacin/nicotinic acid) is a carboxylic acid with a pyridine ring. It is soluble in water and alcohol but insoluble in nonpolar solvents.…”
Section: Introductionmentioning
confidence: 99%
“…Pyridoxine HCl is one of the most essential ingredients and participates in many vital metabolic activities of living cells, i.e., for the production of red blood cells (RBCs) and cells of the immune system, and it maintains proper functioning of nerves. Pyridoxine HCl is an important vitamin for greater than 100 enzyme reactions in the body related to the metabolism of amino acids and proteins. , Due to the complex nature of the vitamins, the thermodynamic, transport, and spectroscopic data are quite informative in understanding the molecular interactions occurring in fluids.…”
Section: Introductionmentioning
confidence: 99%
“…Pyridoxine HCl is an important vitamin for greater than 100 enzyme reactions in the body related to the metabolism of amino acids and proteins. 11,12 Due to the complex nature of the vitamins, the thermodynamic, transport, and spectroscopic data are quite informative in understanding the molecular interactions occurring in fluids.…”
Section: Introductionmentioning
confidence: 99%